2011
DOI: 10.1007/s10534-011-9510-x
|View full text |Cite
|
Sign up to set email alerts
|

The copper-inducible ComR (YcfQ) repressor regulates expression of ComC (YcfR), which affects copper permeability of the outer membrane of Escherichia coli

Abstract: The pathway of copper entry into Escherichia coli is still unknown. In an attempt to shed light on this process, a lux-based biosensor was utilized to monitor intracellular copper levels in situ. From a transposon-mutagenized library, strains were selected in which copper entry into cells was reduced, apparent as clones with reduced luminescence when grown in the presence of copper (low-glowers). One low-glower had a transposon insertion in the comR gene, which encodes a TetR-like transcriptional regulator. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 32 publications
(37 reference statements)
0
49
0
Order By: Relevance
“…In Gram-negative bacteria, copper ions need to be imported into the periplasm first. OmpC and ComC (YcfR) play a role here (57,59). Although a strain deficient in the gene for the NADH: ubiquinone oxidoreductase II (Ndh) suffered a faster inactivation than its parent strain in the presence of copper and tert-butyl hydroperoxide (60), Ndh was not involved in copper tolerance in the absence of this substance (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In Gram-negative bacteria, copper ions need to be imported into the periplasm first. OmpC and ComC (YcfR) play a role here (57,59). Although a strain deficient in the gene for the NADH: ubiquinone oxidoreductase II (Ndh) suffered a faster inactivation than its parent strain in the presence of copper and tert-butyl hydroperoxide (60), Ndh was not involved in copper tolerance in the absence of this substance (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…YcfR has been shown to have a negative role in E. coli biofilm formation only in LB with glucose, likely by decreasing bacterial aggregation and cell surface adhesion as a result of decreased hydrophobicity and increased intracellular indole concentrations (66). Others have reported that YcfR lowers the permeability of the outer membrane to copper (85). The ycfR nucleotide sequence is 81% identical between Salmonella and E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be elucidated whether ComC limits copper acquisition by affecting porin activity or by another mechanism. Under In contrast to many other copper-responsive regulators, ComR does not regulate its own expression (Mermod et al, 2012). It remains unknown to date whether ComR regulates target genes other than comC.…”
Section: Glutamicummentioning
confidence: 98%
“…1). The outermembrane protein ComC reduces the permeability of the outer membrane to copper (Mermod et al, 2012). It remains to be elucidated whether ComC limits copper acquisition by affecting porin activity or by another mechanism.…”
Section: Glutamicummentioning
confidence: 99%